INTEGRAL IMAGE OF PROHOROV CALCULUS ON SPACE OF THE RATIONED CAPACITIES - Глушак, Інна Дмитрівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is proved that Prokhorov metric on the space of normed regular non-additive measures is a particular case of Lipschitz metric constructed using Sugeno integral.